أثر تمرينات تأهيلية في التمزق الجزئي العرضي للعضلة الدالية بدلالة النشاط الكهربائي(EMG) للاعبي كرة اليد الشباب - الحسناوي, احمد يوسف متعب; الرضا, احمد عطشان عبد (Sulaimani Journal for Humanities, 2018)
The problem of study represented in shoulder's muscles injury specifically for handball players, which always happens in early time and repeats without suitable rehabilitation for it. The researchers noted that the deltoid muscles always injured due the using of it for long time in perform the skills by handball players without preparing or developing the muscular strength by usage suitable warmup and training load. The study aimed to prepare special exercises for rehabilitation the injured deltoid muscles for young handball players, and know the effect of the rehabilitation exercises in injury of deltoid muscles by In terms of electrical activity of the muscles (EMG). The researcher used the experimental method, one group with pre-test, middle and posttest design. The community of study consist of the injured young handball players in the southern and middle area in Iraq, the sample of study included 10 players played in Iraqi league (2015 season). The researchers used observation and experimentation and objective tests as a means of gathering information. after pre - test the respondents underwent to first part of rehabilitation program for four weeks, three sessions a week. After that, the middle test was done, then the respondents completed the second part of rehabilitation program for four weeks, three sessions a week, and at the last, the post test had been done. For analyzing the data statistically, researchers used SPSS statistical bag. The researchers concluded the rehabilitation exercises have a positive effect in the development of strength and muscular endurance for injured deltoid muscles, and improving the electrical activity of the muscles (EMG).
Keywords: rehabilitation exercises; Partial rupture of deltoid muscles; electrical activity of themuscles EMG; young handball players